2017
DOI: 10.1016/j.abb.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Signaling by 4-hydroxy-2-nonenal: Exposure protocols, target selectivity and degradation

Abstract: 4-hydroxy-2-nonenal (HNE), a major non-saturated aldehyde product of lipid peroxidation, has been extensively studied as a signaling messenger. In these studies a wide range of HNE concentrations have been used, ranging from the unstressed plasma concentration to far beyond what would be found in actual pathophysiological condition. In addition, accumulating evidence suggest that signaling protein modification by HNE is specific with only those proteins with cysteine, histidine, and lysine residues located in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 131 publications
(120 reference statements)
0
48
0
1
Order By: Relevance
“…HNE is also recognized as a biomarker of oxidative stress, and as such, is involved in (breast) cancer progression [31][32][33]. In accordance with its role are concentrations found in human plasma, where concentrations ranging from 0.1 µM to 1 µM are considered physiological, while 1 µM to 10 µM are considered as "where pathology begins" [34]. Taken that hereditary mutations in breast cancer, as well as conventional cancer treatment strategies, such as chemo-and radiotherapy, cause increases in ROS, which can, in turn, cause lipid peroxidation and HNE formation, these oxidative processes may affect numerous signaling molecules such as HNE activation of NRF2 transcription factor.…”
Section: Discussionmentioning
confidence: 98%
“…HNE is also recognized as a biomarker of oxidative stress, and as such, is involved in (breast) cancer progression [31][32][33]. In accordance with its role are concentrations found in human plasma, where concentrations ranging from 0.1 µM to 1 µM are considered physiological, while 1 µM to 10 µM are considered as "where pathology begins" [34]. Taken that hereditary mutations in breast cancer, as well as conventional cancer treatment strategies, such as chemo-and radiotherapy, cause increases in ROS, which can, in turn, cause lipid peroxidation and HNE formation, these oxidative processes may affect numerous signaling molecules such as HNE activation of NRF2 transcription factor.…”
Section: Discussionmentioning
confidence: 98%
“…High levels of HNE may influence cellular function and behaviour [17]. The formation of cross-linked HNE-protein adducts might notably affect the cellular senescence process and, thus, contribute to aging [3,17,20]. Studies have shown that the generation of HNE-protein adducts can play important pathogenic roles in age-related neurodegenerative diseases, atherosclerosis and cancer [21][22][23][24].…”
Section: Hne Reactivity and Metabolismmentioning
confidence: 99%
“…HNE is degraded to non-toxic or less toxic compounds which are either metabolised or excreted [17]. The key HNE-degrading enzymes are glutathione S-transferases (GST), alcohol dehydrogenases (ADH) and aldehyde dehydrogenases (ALDH) [3,17,28]. In rat hepatocytes, more than half of HNE is metabolised to the GSH-HNE intermediate conjugate [17,29].…”
Section: Hne Reactivity and Metabolismmentioning
confidence: 99%
See 2 more Smart Citations